Economic importance of the Belgian maritime and inland ports – Report 2018 - Ilse Rubbrecht; Koen Burggraeve (National Bank of Belgium, 2020)
This Working Paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2013 - 2018 in terms of value added, employment and investment. Each of these ports play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centers facilitating the commodity flow. In 2018, Belgian ports generated exteuro 32.1 billion in direct and indirect value added (i.e. 7% of Belgian GDP) and employed 249 612 people as full-time equivalents (FTEs) either directly or indirectly (5.9% of Belgian domestic employment including the self-employed). While direct employment in Belgian ports grew by 1% in 2018, thanks to a significant rise recorded in the branches of the ports themselves, direct value added contracted by 2.9%, compared to the record year 2017. The decline in direct value added was particularly noticeable in the non-maritime branches of the ports of Antwerp and Liège. Direct employment at the Belgian ports increased by 1% in 2018 on the back of a significant rise in the number of jobs registered in the cargo handling sector, part of the maritime cluster. All Flemish ports generated additional jobs. Aside from extra employment creation in cargo handling, also other branches generated supplementary jobs. The pattern of investment is closely linked to projects and therefore highly volatile. Direct investments went up for the third year in a row; to a level of almost exteuro 6 billion in 2018. The increase was mainly explained by investment at the port of Antwerp in the context of a merger operation in the shipping companies branch. Based on the figures of maritime traffic, the Flemish ports can be considered as real bridgeheads for trade with the UK. As the current free access for the UK to the Single Market and for EU member states to the UK will cease to apply once the transition periods ends, the shape of the future trade relationship between the EU and the UK will have an impact on the import and export volumes in terms of tonnage. This chapter will try to shed some light on the macroeconomic impact of Brexit on the Belgian economy as a whole. The initially planned publication of this study coincided with the global outbreak of the COVID-19 crisis. Therefore, a brief chapter is devoted to the economic impact of the corona virus on the Belgian ports, more precisely on the port of Antwerp.
Keywords: C13; C43; C67; C81; J21; J49; L91; L92; R11; R15; R41; 330; Belgian ports; microeconomic data; direct effects; indirect effects; input-output table; employment; value added; investment